ANAESTHESIOLOGY AND INTENSIVE CAREPulmonary function tests in the preoperative evaluation of lung cancer surgery candidates. A review of guidelines - Trzaska-Sobczak, Marzena; Skoczyński, Szymon; Pierzchała, Władysław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Before planned surgical treatment of lung cancer, the patient’s respiratory system function should be evaluated. According to the current guidelines, the assessment should start with measurements of FEV1 and DLco. Pneumonectomy is possible when FEV1 and DLco are > 80% of the predicted value (p.v.). If either of these parameters is < 80%, an exercise test with VO2 max measurement should be performed. When VO2 max is < 35 % p.v. or 400 m. Patients considered for lobectomy should be able to climb 3 flights of stairs (12 m) and for pneumonectomy 5 flights of stairs (22 m).